Investigation into psychological contract in ethically disciplined group: a case study of academics in Chinese higher education - Fu, Yao; Xu, Yuan (Frontiers in Psychology, 2023)
Ethical values and beliefs are increasingly realized as an important factor in the operation of psychological contract for its potential role in determining individuals' attitudes towards employment relationship and criteria toby valuinge the mutual exchange. However, to incorporate ethical terms into psychological contract analysis is challenging because they are often confused with relational contract and ethics of professions can be difficult to summarize and interpret. This work has demonstrated how psychological contract operates within academics in Chinese higher education, ann ethically disciplined occupational group that is typically considered ethically disciplined, exampled by academics in Chinese higher education and culturally. From both cultural/social and political/economic perspectives, we believe this is an ideal sample population that exhibits strong constraints from professional ethics and significant bondeds to their identity.Here, we designed a questionnaire survey focusing on transactional/ relational psychological contract, ethical framework and job performance, and Results from statistically analysanalyzed the responses to this survey from 230 Chinese higher education academicsis of questionnaire survey focusing on transactional/ relational psychological contract, ethical framework and job performance.have revealed unique features in this group of professionals, which can be considered anomalous in other occupations. Specifically, these includeIt finds that the sample population perceived psychology contact with a relatively low dependency contribution fromon monetary terms, while ; a strong correlation was observed between ethics and relational terms; . In addition, the influence froma differentiation between emotional and ethical terms in their influences onon job performance was clearly differentiated in statistics;. From analyzing through a mediation model, it suggested an and an intermediated role of ethics between psychological contract and job performance. Findings in this work have demonstrated that ethically disciplined groups exhibit unique features in both their perceptions of psychological contract and its correlation with ethics and job performance, which is anomalous in other occupations. This work provides a protocol demonstrating the role of ethical framework in the operation of psychological contract, particularly within occupational groups that bonded strongly with to their identity/profession and constrained by ethics imposed by the society.